DIAGNOSTICS, CLINICAL COURSE AND EFFECTIVENESS OF TREATMENT OF NEWLY DIAGNOSED YOUNG PATIENTS WITH RESPIRATORY TUBERCULOSIS - I. A. Morozov (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
We observed a group of 103 patients aged 18-30 years with pulmonary tuberculosis; each patient was observed for 12 months. 103 patients with pulmonary tuberculosis underwent a comprehensive clinical, radiological and microbiological examination. The carried out treatment was individualized basing on the presence and prevalence of cavities in the lungs, detection of Mycobacterium tuberculosis in sputum and determination of their drug sensitivity to anti-TB drugs. In 18.4 % of tuberculosis cases diagnosed with chest X-rays, intradermal Mantoux test with 2 TE PPD-L and Diaskintestom® was diagnostically irrelevant. 18.4 % of respiratory tuberculosis cases were detected during preventive chest X-ray and 81.6 % of patients were diagnosed in primary care facilities having referred with symptoms of inflammatory bronchopulmonary disease or concomitant diseases, combined with pulmonary involvement. We can conclude that without fluorography studies of the chest, intradermal Mantoux test with 2 TE PPD-L and Diaskintestom® is not a method for pulmonary tuberculosis timely diagnostics in people aged 18-30 years. The patients with pulmonary tuberculosis aged 18-30 years, diagnosed during preventive fluorography examination of the chest, after 12 months of treatment in 100 % managed to achieve clinical recovery. Same age patients with pulmonary tuberculosis, diagnosed when applying to primary care facilities with symptoms of inflammatory bronchopulmonary disease, after 12 months of treatment achieved clinical recovery only in 79.2 % and 20.8 % of them still had the lung cavities requiring further treatment and applying surgery to remove affected sections of the lungs.